EXTH-45. MICROGLIA-SPECIFIC DISRUPTION OF SIALIC ACID-SIGLEC-9/E INTERACTIONS: A NOVEL IMMUNOTHERAPY AGAINST GLIOBLASTOMA?. (12th November 2021) - Schmassmann, Philip; Martins, Tomás A; Stanczak, Michal; Ritz, Marie-Françoise; Shekarian, Tala; McDaid, Marta; Läubli, Heinz; Hutter, Gregor
Abstract: Recently, 'don't eat me'-signals like CD47 have emerged as novel innate immune checkpoints, enabling cancer cells to evade clearance by phagocytes such as monocyte-derived macrophages (MDM) or microglia (MG). Here, we aim at defining the role of inhibitory Siglec-9 in human and its mouse homologue Siglec-E in MG-centered immunotherapy against GBM. TCGA RNA-sequencing data revealed a significant correlation between high expression of immunoinhibitory SIGLEC9 and poor survival in GBM patients (log-rank p = 0.02). Siglec-E blockade increased murine MG mediated GBM cell in vitro phagocytosis (normalized phagocytosis of 1.00 in isotype vs. 1.76 in anti-Siglec-E antibody, p < 0.001). By employing a CT-2A orthotopic GBM mouse model with MG-specific spatio-temporal deletion of Siglece ( Sall1 CreERT2 x Siglece flox ), we observed high MG-proliferation upon Siglec-E knockdown (Ki-67 + MG 14.8% in Cre - vs. 34.9% in Cre +, p < 0.0001) accompanied by an enhanced microglial GBM-cell uptake (5.6% in Cre - vs. 12.3% in Cre +, p < 0.001). This beneficial response was counteracted by an accentuated influx of pro-tumorigenic MDM in the Cre + group (CD163 high CD86 low MDM of total MDM 47.1% in Cre - vs. 65.3% in Cre +, p = 0.002), which prevented an efficient adaptive anti-tumor immune response and survival benefit. Currently, we are investigating the cross-talk between GBM-associated MG and MDM upon Siglec-E knockdown by scRNAseq of the tumor-infiltrating immune compartment, including TCR-clonotype tracking. By genetically targeting sialic acids, the ligand for Siglec receptors, on CT-2A cells (GNE-KO), we observed a strong innate and adaptive immune response with less exhausted tumor-infiltrating CD8 + T-cells (14.8% in WT vs. 5.9% in GNE-KO, p = 0.003), which resulted in a prolonged survival (30d in WT vs. 41d post-tumor-injection in GNE-KO, p = 0.03). These data identify the sialic-acid-Siglec-E pathway as an anti-phagocytic signal in a pre-clinical GBM model, and demonstrate its therapeutic potential in GBM immunotherapy.